2020
DOI: 10.1177/0284185120940242
|View full text |Cite
|
Sign up to set email alerts
|

Emergency neck MRI: feasibility and diagnostic accuracy in cases of neck infection

Abstract: Background Computed tomography (CT) has traditionally been the first-line imaging method in neck emergencies such as deep neck infections. Due to superior soft-tissue contrast, magnetic resonance imaging (MRI) may be an alternative to CT, also in emergency situations. Purpose To characterize the use of routine MRI in neck emergencies, with an emphasis on clinical feasibility and diagnostic accuracy in cases of neck infection. Material and Methods We conducted a retrospective cohort study of all primary neck MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 16 publications
3
61
0
Order By: Relevance
“…We measured the maximal diameter of the abscesses from post-Gd T1-weighted images. Substantial interobserver agreement for the detection of an abscess has been shown previously [8].…”
Section: Definition Of Imaging Outcomes and Ratingsmentioning
confidence: 58%
See 2 more Smart Citations
“…We measured the maximal diameter of the abscesses from post-Gd T1-weighted images. Substantial interobserver agreement for the detection of an abscess has been shown previously [8].…”
Section: Definition Of Imaging Outcomes and Ratingsmentioning
confidence: 58%
“…Accurate evaluation becomes crucial for detecting abscesses, which usually require prompt surgical exploration. MRI was recently shown to be accurate in detecting abscesses that far exceed those previously reported for CT [ 8 ]. In the same study, the positive predictive value (PPV, fraction of patients with a positive test result who actually have the disease) for the detection of an abscess was 0.95, compared with about 0.80 previously reported for CT. Differentiation between RPE and true retropharyngeal abscess may be especially difficult with CT, with studies showing PPV in the range of 0.50 to 0.80 [ 4 , 13 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR imaging provides superior soft-tissue contrast compared with CT, 7,8 and emergency neck MR imaging is feasible even in acutely ill patients. 9 MR imaging can distinguish between reactive nonsuppurative edema and true abscesses in the deep neck spaces and has a high diagnostic accuracy in the detection of neck infections and abscesses. 9 Therefore, MR imaging might be useful for illustrating the spectrum of tonsillar infections.…”
mentioning
confidence: 99%
“…CT combines fast image acquisition Infection and Drug Resistance 2021:14 and precise anatomical information without field-of-view limitations. Nurminen et al 18 reported that magnetic resonance imaging (MRI) had very high diagnostic accuracy and predictive value for both infections and abscesses, whereas MRI was more complex and time-consuming to read than CT. For these reasons, CT is the first imaging examination of choice in emergency situations, especially in cases of shortness of breath. If an abscess has not yet formed or the scope is small, the patients can be followedup by CT examination or color Doppler ultrasound examination according to the general clinical situation.…”
mentioning
confidence: 99%